Predictive Value of Abdominal CT Based-skeletal Muscle Mass Combined with Critical Illness Score for Prognosis in Older Patients with Intra-abdominal Sepsis - LI Qiujing, SHANG Na, GAO Qian, YANG Li, GUO Shubin (Zhongguo quanke yixue)
Background Intra-abdominal infection is a common etiology of sepsis, and older patients with intra-abdominal sepsis have a high mortality rate. Therefore, it is significant to evaluate the prognosis accurately. Currently, the measurement of skeletal muscle mass derived from computed tomography (CT) has become a research hotspot. Whereas the prognostic value of skeletal muscle mass in older patients with abdominal sepsis is rarely reported. Objective To investigate the prognostic value of the skeletal muscle index (SMI) at the midpoint of the third lumbar vertebra (L3) along with Sequential Organ Failure Assessment (SOFA) score or Acute Physiology and Chronic Health EvaluationⅡ (APACHEⅡ) score in older patients diagnosed with intra-abdominal sepsis. Methods This study was conducted at the Emergency Medicine Clinical Research Center, Beijing Chao-Yang Hospital, Capital Medical University from January 1 to July 31, 2022. A total of 335 older patients with intra-abdominal sepsis were recruited. The participants were divided into survival group (250 cases) and non-survival group (85 cases) based on their survival status during hospitalization. Clinical characteristics and L3 SMI derived from abdominal CT were compared between survival and non-survival groups. Multivariable Logistic regression analysis was used to identify the risk factors of in-hospital mortality in older patients with intra-abdominal sepsis. The receiver operating characteristic (ROC) curves of L3 SMI, SOFA score, APACHEⅡ score, and combined variables for predicting in-hospital mortality were drawn, and the area under the curve (AUC) were calculated and subsequently compared. Results 335 older patients with intra-abdominal sepsis were included, of whom 85 (25.4%) died. There were statistically significant differences in age, BMI, albumin, creatinine, procalcitonin, L3 SMI, Nutritional Risk Screening 2002 (NRS2002), sepsis shock proportion, SOFA score, APACHE Ⅱ score between the two groups (P<0.05). Multivariable Logistic regression analysis revealed that decreased L3 SMI (OR=0.924, 95%CI=0.886-0.964, P<0.001), increased NRS2002 score (OR=1.312, 95%CI=1.086-1.585, P=0.005), increased SOFA score (OR=1.170, 95%CI=1.053-1.300, P=0.004), and increased APACHEⅡ score (OR=1.052, 95%CI=1.003-1.103, P=0.038) were independent risk factors for in-hospital mortality in older patients with intra-abdominal sepsis. The AUCs of L3 SMI, SOFA score, and APACHEⅡ score for predicting the risk of in-hospital mortality were 0.711, 0.740, and 0.742, respectively. L3 SMI combined with SOFA score, or APACHEⅡ score could improve their predictive ability, with AUCs of 0.795 and 0.792, respectively. Conclusion Decreased L3 SMI was an independent risk factor for in-hospital mortality in older patients with intra-abdominal sepsis, The skeletal muscle mass based on abdominal CT combined with critical illness scoring systems could effectively evaluate the prognosis of these patients.